(3GdQSGdI GdMGJejI ef MceI CQSWGWGdjS hTYQ CHj GdWjH GdeJfHis - (3eMeO Hf GdMSf Hf GdeXaQ GdMGJej GdHZOGOj , CHh Ydj,J (B388 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf Mb eG GMJceJ Edjg fahS CHhGdWjH CMeO Hf GdMSjf GdeJfHi s
(3BNQgG (B:s
(3hZGjI GdeaQW ai Sdeg cZGjI JeJ GdQSGdI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B82s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3eYgO OejGW (B((3ehGYX (B23) s
Keywords: (3GdadSaI hGdefWbs